2019
DOI: 10.2319/090418-645.1
|View full text |Cite
|
Sign up to set email alerts
|

Tissue response resulting from different force magnitudes combined with corticotomy in rats

Abstract: Objectives: To evaluate the amount of hyalinization and root resorption after application of light and heavy forces during corticotomy-assisted tooth movement. Materials and Methods: Forty-eight male Wistar rats were used. Eight animals were the control group (day 0). The other 40 animals were randomly divided into two groups using the split-mouth technique: (1) corticotomy combined light force (CLF) and (2) corticotomy combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Split mouth designs have been frequently employed in orthodontics. [32][33][34] They rely on the assumption that high agreements exist between the left and right site. However, this assumption has been rarely validated, even though comparability was suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Split mouth designs have been frequently employed in orthodontics. [32][33][34] They rely on the assumption that high agreements exist between the left and right site. However, this assumption has been rarely validated, even though comparability was suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is used to accelerate OTM, but their impact on root resorption is inconclusive. Corticotomy and corticision have effect on reduction of root resorption during the early stages of OTM, but root resorption was increased with heavy force 207 . Moreover, most surgical methods including alveolar decortication, piezocision, and MOP increase the root resorption, and the degree of root resorption is positively correlated with the degree of surgical injury [208][209][210] , which indicates that the application of these surgical methods should be thought synthetically and prudently.…”
Section: Prevention Of Root Resorptionmentioning
confidence: 96%
“…Some studies have shown that a 10-cN force on rat molars could produce more tooth movement and less root resorption than heavier forces. 36,37 However, some researchers consider a 25-30-cN force as appropriate to induce orthodontic tooth movement in rats. 12,38 Considering the reduction of spring force value along with tooth movement, a 30-cN force was applied in this study.…”
Section: Discussionmentioning
confidence: 99%